2022
DOI: 10.3390/s22197303
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Detection on Chest X-ray and CT Scan: A Review of the Top-100 Most Cited Papers

Abstract: Since the beginning of the COVID-19 pandemic, many works have been published proposing solutions to the problems that arose in this scenario. In this vein, one of the topics that attracted the most attention is the development of computer-based strategies to detect COVID-19 from thoracic medical imaging, such as chest X-ray (CXR) and computerized tomography scan (CT scan). By searching for works already published on this theme, we can easily find thousands of them. This is partly explained by the fact that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 129 publications
0
2
0
Order By: Relevance
“…Over the past few years, there has been a surge in studies exploring deep learning techniques to diagnose COVID-19 and pneumonia. Systematic reviews of AI-enabled COVID-19 detection can be found in [1][2][3] in 2021, [4][5][6][7][8][9][10] in 2022, and [11][12][13] in 2023. While all reviews delved into deep learning neural networks and medical image databases, there were apparent shifts in focus, from the feasibility of deep learning to this aim and limited databases in 2021, to model performance comparison and database survey in 2022, and to model enhancement/development and real-world applications recently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, there has been a surge in studies exploring deep learning techniques to diagnose COVID-19 and pneumonia. Systematic reviews of AI-enabled COVID-19 detection can be found in [1][2][3] in 2021, [4][5][6][7][8][9][10] in 2022, and [11][12][13] in 2023. While all reviews delved into deep learning neural networks and medical image databases, there were apparent shifts in focus, from the feasibility of deep learning to this aim and limited databases in 2021, to model performance comparison and database survey in 2022, and to model enhancement/development and real-world applications recently.…”
Section: Introductionmentioning
confidence: 99%
“…These studies either used chest X-ray images or CT scans [17][18][19][20][21][22] and were designed as either binary or multi-class classifications [23,24]. In general, the model classification accuracy was higher using chest X-ray images (90%+) than using CT (~85%) and was higher (1-5%) in binary than multi-class classifications [10,25,26]. To remedy data shortages, various techniques of data augmentation were used, including scaling, rotation, shifting, and image filtering such as grayscale and Gaussian blur [27][28][29].…”
Section: Introductionmentioning
confidence: 99%